(untitled) (Revista Educação, Artes e Inclusão, 2024)
The article brings reflections on the transmutations of the body in the performance manifesto A Arte Carnal (1990-95) by the French artist Orlan (1947-). Through performative actions in the media and physical space, in the theoretical field of the arts, this qualitative, bibliographical and exploratory research aims to relate standards imposed by the media and art materialized in Orlan’s body. How are bodies affected within this relationship between body and identity canonized by art and fashion? In this show body, unnatural elements are incorporated, such as prostheses, real plastic surgeries and/or manipulated by computer programs. The body as corporeity is the subjective existence of the subject and through it it is possible to perceive the world and relate to others. Orlan reconstructs her self-portrait, manipulating her own flesh, through invasive procedures, questioning the media influences and the History of the Arts exerted on the body of contemporary women. Her body establishes itself as a social mirror, resulting in the understanding of the body as a consequence of social conflicts, misogynistic discourses, subjectivity and identity. Causing aesthetic enjoyment, she explores and problematizes these relationships in her own female body transformed into an art object in the service of art.